Access to artemisinin-based combination therapy (ACT) and quinine in malaria holoendemic regions of western Kenya - Watsierah, Carren A (BioMed Central, 2014)
BACKGROUND: Artemisinin-based combination therapy (ACT) has been adopted as the most effective treatment against malaria in many endemic countries like Kenya while quinine has remained the second line. The objective of the current study was to assess access to Kenya’s policy recommended anti-malarials, ACT and quinine in the public, private and not-for-profit drug outlets in western Kenya. METHODS: A cross-sectional survey using purposive sampling of 288 outlets (126 public, 96 private, 66 not-for-profit) was conducted in western Kenya in two regions with varying Plasmodium falciparum endemicities. Information on access (availability, price, affordability) on ACT and quinine was collected using the WHO and Healthcare Associated Infection (HAI) standardized methodologies for availability, prices and affordability of drugs. From a Ministry of Health database, the following were included in the analyses: one (1) main public hospital, followed by random selection of five hospitals under this main facility. Eight other public outlets under each of the hospitals were selected, to a total of 96. Matching number of private outlets (n = 96), all (66) not-for-profit outlets and additional 30 public health facilities were sampled to get the required sample size of 288. RESULTS: More public 111 (88.1%) and not-for-profit 27 (40.9%) outlets stocked subsidized ACT (artemether-lumefantrine, AL). Other artemisinin-based combinations were widely available for both children 93 (96.9%) and adults 82 (85.0%) in private outlets. Frequent stock-outs were in public in 106 (84%), reporting three times or more stock-outs in three months. Subsidized ACT (AL) was sold at median price of USD 0.94 and 0.75 in private and not-for-profit outlets respectively. The costs was higher than recommended price of USD 0.5 and requiring up to 0.20-0.25 days of disposable income for households in lowest economic status. CONCLUSION: There is low availability of subsidized ACT (AL) and higher frequency of stock-outs in government facilities, while private sector sells AL at higher prices, thus making it less affordable to many households. These factors determine the adherence to the dosing schedules during the treatment course and thus the evaluation of the subsidy policy, its implementation and role in malaria burden in this region is compulsory.